An exploration of maternal support to children’s academic achievement in low‑cost private schools in Lahore - Niaz, A (2017)
With an increased recognition of the poor quality and limited availability of schools provided by the government, low cost private schools are experiencing exponential growth across Pakistan. By drawing on qualitative, semi structured interviews with 15 low income mothers of children enroled in primary low cost private schools in Lahore, this study explores the way mothers are responding to this development, focussing on maternal conceptualisations of the value of education, and the behaviours they adopt at home and in relation to the school in order to support their children’s academic achievement. This study finds that mothers tend to prefer private schools in place of public schools. The responses indicate this is due to increased private school availability within poorer communities, English language being offered as the medium of instruction, the presence of more and qualified teachers and the availability of basic infrastructure such as running water and electricity. Qualitative inquiries regarding behaviours suggest, despite limited resources and at times, illiteracy, mothers are determined to engage with their children’s academic performance in a variety of ways at home and in relation to the school. At home, they tend to involve themselves by checking their children’s homework, assisting in exam preparation and encouraging siblings to provide academic guidance to one another. Importantly, they also enrol their children in after school private tutoring as a way to provide indirect academic support to their children. In relation to the school, mothers regularly attend parent teacher meetings, and if necessary, visit the school in order to discuss their child’s progress, both academic and discipline related. Importantly, their interaction with the school is mostly limited to parent teacher meetings that are initiated by the teachers. The findings of this study emphasise the need for future scholarly attention on exploring low income mothers prioritisation of private tutoring as a popular form of indirect academic support to their children. Additionally, the findings call for an investigation of the limited interaction between low cost schools and parents, particularly mothers, as they appear to be the more involved parents in low income communities in Lahore and exhibit a desire to engage more actively.